Penggunaan Vitamin D3 Oral Dosis Tinggi - Esther Kristiningrum (Cermin Dunia Kedokteran, 2022)
Vitamin D is a fat-soluble vitamin with an important role in various skeletal and non-skeletal physiological functions. Vitamin D deficiency has been found in many countries including Indonesia, and has been associated with an increased risk of various diseases. Vitamin D supplementation or even high-dose vitamin D therapy is often necessary to maintain or to achieve optimal vitamin D status, especially if rapid correction is required and/or as adjunctive therapy for other diseases. Various clinical trials have shown that high-dose oral vitamin D3 therapy is effective and relatively safe for vitamin D deficiency patients.